Detection of nitrifiers and evaluation of partial nitrification for wastewater treatment: A review. (December 2015) - Ge, Shijian; Wang, Shanyun; Yang, Xiong; Qiu, Shuang; Li, Baikun; Peng, Yongzhen
Highlights: Current molecular technologies to identify and detect AOB/NOB are summarized. Strategies for partial nitrification via nitrite are critically reviewed. Combination of partial nitrification and Anammox benefits wastewater treatment. Existing problems and directions for future research in partial nitrification are suggested. Abstract: Partial nitrification has gained broad interests in the biological nitrogen removal (BNR) from wastewater, since it alleviates carbon limitation issues and acts as a shortcut nitrogen removal system combined with anaerobic ammonium oxidation (Anammox) process. The occurrence and maintenance of partial nitrification relies on various conditions, which favor ammonium oxidizing bacteria (AOB) but inhibit or limit nitrite oxidizing bacteria (NOB). The studies of the AOB and NOB activities have been conducted by state-of-the-art molecular techniques, such as Polymerase Chain Reaction (PCR), Quantitative PCR, denaturing gradient gel electrophoresis (DGGE), Fluorescence in situ hybridization (FISH) technique, Terminal Restriction Fragment Length Polymorphism (T-RFLP), Live/Dead BacLight, and quinone profile. Furthermore, control strategies for obtaining partial nitrification are mainly focused on the pH, temperature, dissolved oxygen concentration, real-time aeration control, sludge retention time, substrate concentration, alternating anoxic and aerobic operation, inhibitor and ultrasonic treatment. Existing problems and further perspectives for the scale-up of partial nitrification are also proposed and suggested.